2007
DOI: 10.1089/pho.2006.2032
|View full text |Cite
|
Sign up to set email alerts
|

Laser Therapy in the Treatment of Carpal Tunnel Syndrome: A Randomized Controlled Trial

Abstract: In using LLLT, (1) there was no difference relative to pain relief and functional capacity during the follow-up in CTS patients; (2) there were positive effects on hand and pinch grip strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 23 publications
2
40
0
2
Order By: Relevance
“…Furthermore, it may alter the ion flow in membrane channels, therefore leading to decreased inhibitory post-synaptic potential and increased speed flow in neural cells. Other modalities such as local corticosteroid injection (Deniz et al 2012) and surgical decompression (Evcik et al 2007) can significantly improve SNCV and the sensory nerve action potential amplitude of the median nerve. However, others have reported no improvement (Gurcay et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may alter the ion flow in membrane channels, therefore leading to decreased inhibitory post-synaptic potential and increased speed flow in neural cells. Other modalities such as local corticosteroid injection (Deniz et al 2012) and surgical decompression (Evcik et al 2007) can significantly improve SNCV and the sensory nerve action potential amplitude of the median nerve. However, others have reported no improvement (Gurcay et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The present study does not support the use of LLLT for pain reduction. Interestingly, a second study using only one laser color on 81 patients found similar findings [7]. The benefit of the MM treatment is probably related to heat.…”
Section: Discussionmentioning
confidence: 66%
“…High power lasers are commonly used in surgical settings for their thermal effects enabling them to cut, coagulate, and evaporate tissues [5]. Lower-level laser treatment (LLLT) has non-thermal effects but may stimulate cell function [7]. This may be caused by the photochemical reactions in the cells upon laser light irradiation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In a recent prospective, randomized, placebo-controlled trial Evcik, et al reported positive effects on hand and pinch grip strengths after low-level laser therapy. 28 Beneficial effects of the combination of laser therapy with other methods as night orthopedic splint 25 or magnetic stimulation 29 were also reported.…”
Section: Discussionmentioning
confidence: 99%